Evaluation of Neutron Component in Patients under High Energy Radiotherapy By Means of an On Line and In Vivo procedure - Exposito, M. R.; Palma, B. A.; Terron, J. A.; Gomez, F.; Domingo, C.; Barquero, R.; Sanchez-Doblado, F.; Hospital Universitario Virgen Macarena, E-41009, Sevilla (AIP conference proceedings, 2010)
The use of improved radiotherapy methods has raised the concern about second cancer induction. Epidemiological studies have shown a major incidence of secondary cancer in radiotherapy patients compared to patients subjected to another type of treatment. In this regard, it is important to determine the peripheral dose received by the patient during the treatment. While photon doses have been deeply contemplated, neutron contamination in high energy photon beams is still a subject of research and discussion. In the present work, we introduce a new procedure based on a digital device that allows real time neutron contamination evaluation. Several irradiations of an anthropomorphic phantom have been carried out in a variety of facilities and treatments. The purpose was to correlate the measurements from the digital detector with the neutron doses obtained in the phantom by Monte Carlo simulations and experimental measurements. A model has been designed to calculate the organ equivalent dose and risk estimates during any therapeutic session. The procedure has been used to monitor more than 1000 patients showing its applicability in clinical routine. It can be used both for inductive and retrospective studies with a reasonable uncertainty. Thus, this could provide the necessary information to complement the dosimetry of patient and estimate the treatment risk.